PERAN PENGELOLAN KELAS DALAM KEMAMPUAN REGULASI DIRI PADA SISWA SELAMA DI KELAS - Berliana Henu Cahyani (Universitas Sarjanawiyata Tamansiswa, 2012)
ABSTRACTThe study aims at understanding the role of classroom management in student's regulation during the class. The Research subject involves four, ten years male and female Elementary student's. Based on the data analysis, it can he concluded that the self regulation of the students during the class consist of ability to focus, ability to find instruction, ability to monitor, ability to be involved actively in class and metacognitive talk. The classroom management consist of ability to get students involve actively, ability in managing the class distraction and ability to manage time efficiently.Â Key words: Self regulation, Classroom Management.